Effect of spiritual care programs on anxiety and quality of life of chronic respiratory patients - Sadegh Yoosefee; Fereshteh - Javaheri Tehrani; Hossein Azarpira (Journal of Education and Health Promotion)
BACKGROUND: Chronic respiratory disease is currently the third most common cause of death worldwide and is associated with reduced quality of life, anxiety, and depression. The purpose of this study is to determine the effectiveness of spiritual care programs on anxiety and quality of life of chronic respiratory patients. MATERIALS AND METHODS: This semi-experimental study was conducted on chronic respiratory patients in 2023 at Shahid Modares Hospital in Saveh city. The spiritual care program was held during five consecutive sessions for 2 hours for the test group. All patients completed the pretest, and then 1 month after the end of the intervention, they were evaluated in terms of anxiety and quality of life. Block randomization method was used to allocate patients. RESULTS: There was a significant relationship between situational anxiety and all demographic variables. A significant relationship was found between trait anxiety and gender, insurance, and history of surgery. The results showed that there is a significant relationship between different dimensions of quality of life with some demographic variables such as age, income, gender, and history of surgery. The score of situational and trait anxiety in the test and control groups did not show a significant difference after the intervention (P value = 0.09), but this difference was significant in the case of trait anxiety (P value = 0.01). CONCLUSION: The correct inclusion of spirituality in the daily clinical routine can reduce patients’ anxiety and have significant positive effects on patients by creating comfort, increasing adherence to treatment and improving quality of life.